CLOUD TECHNOLOGIES AND ONLINE TOOLS AS A MEANS OF DEVELOPING FUTURE ENGLISH TEACHERS’ DIGITAL COMPETENCE - Yarema, Olena (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article examines the relevance of utilizing cloud technologies and online tools as a powerful means for developing digital competence in the process of training future English teachers. It explores the key aspects and components of digital competence essential for a modern educator. The possibilities of integrating cloud services (such as Google Workspace and Microsoft 365) into the educational process are identified and substantiated.